2016
DOI: 10.1002/anie.201610353
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Nanofibrillar Thermoreversible Hydrogel for Growth and Release of Cancer Spheroids

Abstract: Growth of three-dimensional cancer spheroids (CSs) in man-made hydrogels mimicking natural extracellular matrix is an important and challenging task. Herein, we report on a supramolecular temperature-responsive hydrogel designed for the growth and subsequent release of CSs. A filamentous hydrogel was formed at 37 °C from an aqueous suspension of cellulose nanocrystals surface-functionalized with temperature-responsive polymer molecules. The encapsulation of cells in the hydrogel enabled effective growth of CSs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 46 publications
1
54
0
1
Order By: Relevance
“…There is a growing interest in using CNCs in nanomedicine, due to their biocompatibility, as well as their asymmetric (rod‐like) shape facilitating prolonged blood circulation time and possible cellular uptake . Furthermore, the hydroxyl groups on the CNCs surface are amenable for attachment of polymer molecules or imaging and therapeutic agents . Since C‐dot/CNC NPs can be used as biotags for labeling, sensing, and therapeutics, we examined their biocompatibility by culturing MCF‐7 breast cancer cells for 24 and 48 h in suspensions of hybrid NPs with concentrations from 0.00001 to 0.1 wt% in cell culture media.…”
Section: Resultsmentioning
confidence: 99%
“…There is a growing interest in using CNCs in nanomedicine, due to their biocompatibility, as well as their asymmetric (rod‐like) shape facilitating prolonged blood circulation time and possible cellular uptake . Furthermore, the hydroxyl groups on the CNCs surface are amenable for attachment of polymer molecules or imaging and therapeutic agents . Since C‐dot/CNC NPs can be used as biotags for labeling, sensing, and therapeutics, we examined their biocompatibility by culturing MCF‐7 breast cancer cells for 24 and 48 h in suspensions of hybrid NPs with concentrations from 0.00001 to 0.1 wt% in cell culture media.…”
Section: Resultsmentioning
confidence: 99%
“…Kumacheva's research is focused on soft matter, in particular polymer materials science, nanoscience, polymers in biological systems, and microfluidics. Her report on a supramolecular nanofibrillar thermoreversible hydrogel is published in this issue …”
Section: Awarded …mentioning
confidence: 98%
“…Ideally, the generated cell spheroids are expected to release in some circumstances. It was reported that a kind of nanofibrillar thermoreversible hydrogel was formed by temperature‐responsive polymer poly( N ‐isopropylacrylamide) (PNIPAM) grafted cellulose nanocrystals (CNCs) . Cancer cells were encapsulated in this hydrogel and gradually formed spheroids at 37 °C, which could be released by cooling‐induced hydrogel liquefaction (Figure 7b).…”
Section: Applications Of 3d Biomaterialsmentioning
confidence: 99%
“…b) Cancer spheroids formed and released on demand a thermoreversible hydrogel. Reproduced with permission . Copyright 2016, Wiley‐VCH.…”
Section: Applications Of 3d Biomaterialsmentioning
confidence: 99%